Psychological Treatments for Alexithymia: A Systematic Review - Kanako Tsubaki; Eiji Shimizu (Behavioral Sciences)
Alexithymia, a psychological condition characterized by emotional suppression, is positively correlated with depression and anxiety and can develop into various mental disorders. Although alexithymia affects 10% of the symptomatic population and 25% of psychiatric patients, there has been a paucity of intervention studies. Even though several effective psychological treatments, including cognitive behavioral therapy (CBT), have been tested in recent years, there is a lack of comprehensive reviews on their efficacy. The objectives of this systematic review were to explore and synthesize findings from recent randomized controlled trials (RCTs) about psychological treatments, with the following inclusion criteria: (1) published from 2010 to 2024; (2) full text being available in English; (3) peer-reviewed journals; and (4) baselines and outcomes measured by TAS-20 and raw data were provided. We excluded non-psychological studies and studies involving mindfulness and DBT. We searched electronic databases (PubMed, PsycInfo, and Google Scholar) and found 18 RCTs and 21 arms for alexithymia, with a combined total of 1251 participants. Fourteen arms (67%) investigated the effect of CBT on alexithymia, including acceptance and commitment therapy (seven arms), behavioral activation therapy (two arms), schema therapy, and compassion-focused therapy. The results indicated that most psychological interventions significantly decreased TAS-20, illustrating a showcase of treatments from each trial with different effect sizes (within-intervention group, ranging from 0.41 to 13.25). However, due to the heterogeneity between the studies, this review study may not be conclusive enough to make each intervention standardized. Further high-quality RCTs with larger sample sizes and more consistent methodologies are needed, and corrective findings from such studies should be applied to produce more robust evidence-based psychological interventions for treating alexithymia.